Planning Dewan Masjid Indonesia Dalam Pengembangan Media Dakwah Digital Di Sumatera Utara - Rafi, Ahmad Mustofa; Lahmuddin, Lahmuddin (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2026)
The development of information technology has encouraged transformation in Islamic da'wah strategies, including by religious institutions such as the Indonesian Mosque Council (DMI). This research aims to analyze the strategic planning of DMI North Sumatra in developing da'wah through digital media. This research uses a qualitative approach with data collection methods in the form of observation, in-depth interviews, and document review of the North Sumatra DMI management. The results showed that DMI realizes the importance of digitalization of da'wah in reaching a wide community, especially the younger generation who are active on social media such as YouTube, Facebook, and Instagram. DMI's institutional strategy includes developing technology-savvy human resources, strengthening digital infrastructure, and collaboration with other digital da'wah communities and institutions. However, the implementation of this strategy is faced with various challenges such as limited budget, uneven internet access, and lack of experts in the digital field. This research contributes to enriching institutional-based digital da'wah literature and becomes a practical reference for religious institutions in facing the challenges of the digital era.